2017
DOI: 10.1080/10410236.2017.1353868
|View full text |Cite
|
Sign up to set email alerts
|

Web-based Health Information Seeking and eHealth Literacy among Patients Living with Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Many people living with Chronic Obstructive Pulmonary Disease (COPD) have low general health literacy; however, there is little information available on these patients' eHealth literacy, or their ability to seek, find, understand, and appraise online health information and apply this knowledge to address or solve disease-related health concerns. A nationally representative sample of patients registered in the COPD Foundation's National Research Registry (N = 1,270) was invited to complete a web-based survey to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 113 publications
9
86
2
Order By: Relevance
“…The main characteristics of the sources reviewed were the implementation of an intervention to promote self‐management of the patients' disease(s) and identify behaviour effects and promotion of regimen adherence. Interventions included mobile phone applications (Baron, Hirani, & Newman, ; Hardinge et al, ), gaming (Hickman, Clochesy, Pinto, Burant, & Pignatiello, ), telehealth that included telephone or video streaming (Cameron et al, ; CottrellGalea, O'Leary, Hill, & Russell, ; Fors et al, ; Kennedy et al, ), self‐management programmes (Bratzke, ; Cutler et al, ; Devan et al, ; Fortin, Chouinard, Diallo, & Bouhali, ; Horrell et al, ; Lin, Liu, Hsu, & Tsai, ; Win et al, ), social media (van Berkel et al, ; Wilson et al, ), surveys addressing self‐efficacy (Henselmans et al, ; Koch et al, ; Roncoroni, Tucker, Wall, Wippold, & Ratchford, ; Wu et al, ) and health literacy survey (Mackey, Doody, Werner, & Fullen, ; Stellefson et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the sources reviewed were the implementation of an intervention to promote self‐management of the patients' disease(s) and identify behaviour effects and promotion of regimen adherence. Interventions included mobile phone applications (Baron, Hirani, & Newman, ; Hardinge et al, ), gaming (Hickman, Clochesy, Pinto, Burant, & Pignatiello, ), telehealth that included telephone or video streaming (Cameron et al, ; CottrellGalea, O'Leary, Hill, & Russell, ; Fors et al, ; Kennedy et al, ), self‐management programmes (Bratzke, ; Cutler et al, ; Devan et al, ; Fortin, Chouinard, Diallo, & Bouhali, ; Horrell et al, ; Lin, Liu, Hsu, & Tsai, ; Win et al, ), social media (van Berkel et al, ; Wilson et al, ), surveys addressing self‐efficacy (Henselmans et al, ; Koch et al, ; Roncoroni, Tucker, Wall, Wippold, & Ratchford, ; Wu et al, ) and health literacy survey (Mackey, Doody, Werner, & Fullen, ; Stellefson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Koch et al () described support systems as being formal—health organization groups—and informal—peer groups and family. Several reviewed articles identified a lack of support, either formal or informal, being a barrier to self‐efficacy and positive patient outcomes (Cameron et al, ; Fors et al, ; Henselmans et al, ; Koch et al, ; Stellefson et al, ; Willis, ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the benefits and rising interest in the field [56,57], many MHapps may lack robust scientific grounding [52,[58][59][60]. Similar trends in health information seeking may be observed with blogging [61,62], and microblogging [25,63].…”
Section: Mobile Apps For Mental Health Supportmentioning
confidence: 69%
“…There is growing interest in how Internet and social media use impacts patients with COPD [27]. Social media, particularly platforms that provide support for chronic illnesses (e.g., COPD), extend patients' access to informational and emotional resources enabling them to better cope with their illness [8].…”
Section: Perceived Online Social Supportmentioning
confidence: 99%
“…Interestingly, a greater perception of online social support existed among participants with COPD, who were younger and had low COPD knowledge. Although there is evidence that greater respiratory symptom severity predicts patients' Internet use [27,32], research has demonstrated that high COPD knowledge and less severe symptoms are associated with a higher degree of eHealth literacy (i.e., ability to access, understand, and evaluate online information) [27]. Patients who are at a critical point of illness identity negotiation may not be able to maximize the potential of online social support, because they do not have the optimal skills to do so.…”
Section: Principal Findingsmentioning
confidence: 99%